2014
DOI: 10.1007/s00167-014-2849-0
|View full text |Cite
|
Sign up to set email alerts
|

No radiographic difference between patient-specific guiding and conventional Oxford UKA surgery

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 10 publications
5
27
0
Order By: Relevance
“…In our study, improvement was observed in both groups at 3 months and 1 year without any difference between the two groups. We had to recut the tibial plateau in 10% of our PSI UKA cases; this number is lower than in the Bell et al [6] series reporting 43% of perioperative modifications, but higher than the Kerens et al series (no perioperative modification in 30 PSI UKA) [14]. The number of intraoperative changes in our experience was limited but not null, and this may be related first to the time spent by the surgeon on edition and validation of the preoperative planning and second to the fact that we would not accept intraoperatively an inappropriate cut.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In our study, improvement was observed in both groups at 3 months and 1 year without any difference between the two groups. We had to recut the tibial plateau in 10% of our PSI UKA cases; this number is lower than in the Bell et al [6] series reporting 43% of perioperative modifications, but higher than the Kerens et al series (no perioperative modification in 30 PSI UKA) [14]. The number of intraoperative changes in our experience was limited but not null, and this may be related first to the time spent by the surgeon on edition and validation of the preoperative planning and second to the fact that we would not accept intraoperatively an inappropriate cut.…”
Section: Discussionmentioning
confidence: 64%
“…Jaffry et al [11] investigated implant positioning among PSI UKA, conventional instrumented UKA, and robotic-assisted UKA; their results showed that PSI UKA provided more accurate positioning than conventional instrumentation, no difference between robot and PSI UKA, and finally concluded that PSI UKA took half the time as robotic-assisted UKA to implant. Recently, Kerens et al [14] compared radiographic positioning of implants in 30 conventional Oxford UKA (Biomet Inc, Warsaw, IN, USA) compared with 30 patientspecific guided Oxford UKA. They found no statistically differences between the two groups, except for the positioning of the femoral component in the frontal plane (better in the PSI group).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the use of PSI in medial UKR (MUKR) surgery, Trong et al [21] reported excellent implant alignment when comparing patients' post-operative CTs to pre-operative plans. Kerens et al [22] found that PSI improved the position of the femoral component in the frontal plane, but had no effect on other implant placement parameters. However, Ollivier et al [23] found no differences in functional score, gait, lower limb alignment or implant positioning between PSI and conventional instrumentation.…”
Section: Discussionmentioning
confidence: 99%
“…There was no control group in this study, and the femoral component was not assessed, although the authors did note this, explaining that for this implant, femoral component orientation is based on the tibial cut. Kerens et al 41 compared radiographic positioning of implants in 30 conventional Oxford UKA compared with 30 Patient Specific Guided (PSG) Oxford UKA. They found no statistically or clinically significantly differences between the two groups, except for the positioning of the femoral component in the frontal plane.…”
Section: Haptic Robotic Systemsmentioning
confidence: 99%